The Phenomenon of Dolanan Song in the Life of Modern Javanese ChildrenRunning head: Dolanan Song for Modern Javanese Children - Wadiyo Wadiyo; Slamet Haryono; Joko Wiyoso (Universitas Negeri Semarang, 2021)
The development of community civilization seems to have an effect on the artistic life of the community. A phenomenon that can clearly be seen is the emergence of an artistic life that continues to develop from time to time, including children's songs that were used as a play song. The purpose of this study is to provide a concrete picture of the existence of the dolanan song for children who lived in the world of Javanese environment nowadays. The research method applied is descriptive qualitative. The research location was in Central Java, especially Surakarta, Banyumas, and the northern coast of Java. Data collection techniques were taken by using interview techniques, document studies and observation. The analytical technique applied is descriptive qualitative analysis using source data triangulation. The results of the study indicated that the phenomenon of the existence of Tembang Dolanan for children prominently developed in the form of children's songs in general as a form of individual expression that is not used as a means of playing with peers. Children are more familiar with popular Javanese songs which are widely used as a means of art by adults in various forms which are widely spread through various media. Likewise, what is used in any form that develops in the family, school, and community. Children's songs in Javanese language namely tembang dolanan in particular do not develop as Javanese songs which are consumed by adults.